Atraumatic needles for lumbar puncture: why haven't neurologists changed?. Issue 1 (8th September 2015) - Davis, A; Dobson, R; Kaninia, S; Giovannoni, G; Schmierer, K
Abstract : Diagnostic lumbar puncture is a key procedure in neurology; however, it is commonly complicated by post-lumbar puncture headache. Atraumatic needle systems can dramatically reduce the incidence of this iatrogenic complication. However, only a minority of neurologists use such needles. In this paper, we discuss possible reasons why neurologists have not switched to new technology, looking more at diffusion of innovation rather than lack of evidence. We suggest ways to overcome this failure to adopt change, ranging from local interventions to patient empowerment.